The spread of artemisinin-resistant Plasmodium falciparum in the Greater Mekong Subregion: a molecular epidemiology observational study - Imwong, M; Suwannasin, K; Kunasol, C; Sutawong, K; Mayxay, M; Rekol, H; Smithuis, F; Hlaing, T; Tun, K; van der Pluijm, R; Tripura, R; Miotto, O; et al. (Elsevier, 2017)
BACKGROUND: Evidence suggests that the PfKelch13 mutations that confer artemisinin resistance in falciparum malaria have multiple independent origins across the Greater Mekong subregion, which has motivated a regional malaria elimination agenda. We aimed to use molecular genotyping to assess antimalarial drug resistance selection and spread in the Greater Mekong subregion. METHODS: In this observational study, we tested Plasmodium falciparum isolates from Myanmar, northeastern Thailand, southern Laos, and western Cambodia for PfKelch13 mutations and for Pfplasmepsin2 gene amplification (indicating piperaquine resistance). We collected blood spots from patients with microscopy or rapid test confirmed uncomplicated falciparum malaria. We used microsatellite genotyping to assess genetic relatedness. FINDINGS: As part of studies on the epidemiology of artemisinin-resistant malaria between Jan 1, 2008, and Dec 31, 2015, we collected 434 isolates. In 2014-15, a single long PfKelch13 C580Y haplotype (-50 to +31·5 kb) lineage, which emerged in western Cambodia in 2008, was detected in 65 of 88 isolates from northeastern Thailand, 86 of 111 isolates from southern Laos, and 14 of 14 isolates from western Cambodia, signifying a hard transnational selective sweep. Pfplasmepsin2 amplification occurred only within this lineage, and by 2015 these closely related parasites were found in ten of the 14 isolates from Cambodia and 15 of 15 isolates from northeastern Thailand. C580Y mutated parasites from Myanmar had a different genetic origin. INTERPRETATION: Our results suggest that the dominant artemisinin-resistant P falciparum C580Y lineage probably arose in western Cambodia and then spread to Thailand and Laos, outcompeting other parasites and acquiring piperaquine resistance. The emergence and spread of fit artemisinin-resistant P falciparum parasite lineages, which then acquire partner drug resistance across the Greater Mekong subregion, threatens regional malaria control and elimination goals. Elimination of falciparum malaria from this region should be accelerated while available antimalarial drugs still remain effective. FUNDING: The Wellcome Trust and the Bill and Melinda Gates Foundation.